Confining Carboxylized Carbon Nanotube for Phosphorescence Afterglow with Optical Memory Plasticity. Issue 6 (15th January 2022) - Wu, Yue‐Yue; Liu, Lan; Zou, Jia‐Hao; Liu, Ju‐Qing; Hu, Yi‐Chun; Ban, Chao‐Yi; Li, Fei‐Yang; Li, Zi‐Fan; Zhang, He‐Shan; Zhou, Zhe; Zhao, Jian‐Feng; Xiu, Fei; et al.
Abstract: Afterglow materials are of primary interest in optoelectronics and bioelectronics. Here, a long‐lived phosphorescence afterglow is reported from carboxylated carbon nanotubes (c‐CNTs) confined within boron oxynitride (BNO). The formation of covalent and hydrogen bonds in c‐CNT@BNO enhances the rigidity of the hybrid structure and alleviates the non‐radiative deactivation of excited triplet states, leading to room‐temperature phosphorescence (RTP). The afterglow material exhibits an ultra‐long RTP lifetime of up to 476.6 ms, with an afterglow time of 4.0 s, distinguishable by naked eyes. This unprecedented feature makes c‐CNT act like a light‐sensitive neuron and it is possible to achieve memorizing−forgetting behavior in the form of optical memory plasticity, owing to photons' capture‐and‐slow‐release process. In analogy to the biological brain, both memory strength and forgetting time are proportional to learning exercise, including the intensity and time of irradiation training. The study provides an effective protocol for the synthesis of afterglow nanomaterials, extending their application to brain‐like intelligent technology. Abstract : Confining carboxylized carbon nanotube (c‐CNT) with covalent CO and hydrogen bonds produces long‐lived room‐temperature phosphorescence emission, with a lifetime of 476.6 ms and an afterglow time of 4.0 s. This afterglow behavior enables c‐CNT as a visual neuron to emulate the dynamic memorizing and forgetting process, with the capability of typically optical memory plasticity.